KOMPETENSI LITERASI DATA DAN INFORMASI MEDIA SOSIAL APARATUR PEMERINTAH DESA CIBURIAL DAN KELOMPOK MASYARAKAT INFORMASI - Windyaningrum, Rachmawati (Jurnal Common, 2023)
Ciburial Village developed an information system through social media as a medium for disseminating village information. The social media that are actively managed by Ciburial Village consist of Twitter, Facebook, Instagram, Youtube, and Pinterest. Information management on social media brought Ciburial Village as the first winner of the Best Social Media Management in West Java at the Jabar Juara Award event in 2020. This study aims to reveal the competence of data and information literacy of ciburial village government officials and information community groups. The research method used is qualitative with case studies. The primary data collection technique is through non-participant observation, in-depth interviews, and focuses group discussions, while secondary data is obtained through literature studies of books, journals, archives or village government documents, and internet searches. The data analysis used is the Miles and Huberman model and data triangulation is carried out by triangulation of data, source, and time as a data validity technique. The results of the study show that data literacy competence is shown in the expertise of ASN and Ciburial Village Information Community Groups in activating social media to support the expansion of village information dissemination. Information needs are adjusted to the needs of the community, namely village activities and the potential of the village as a tourist village. The evaluation carried out is to evaluate the activity of the community in accessing Instagram, because there are still many people who have not fully accessed social media. Keywords: Competence, Literacy, Social Media, Instagram